Functionally graded poly(dimethylsiloxane)/silver nanocomposites with tailored broadband optical absorption - Nikolaou, Petros; Mina, C.; Constantinou, Marios; Koutsokeras, Loukas E.; Constantinides, Georgios; Lidorikis, E.; Avgeropoulos, Apostolos; Kelires, Pantelis C.; Patsalas, Panos A. (My University, 2015)
© 2014 Elsevier B.V. All rights reserved. In this work, we produce functionally graded nanocomposites consisting of silver (Ag) plasmonic nanoparticles (PNPs) supported in a poly(dimethylsiloxane) (PDMS) matrix. PDMS was selected due to its high optical transparency, nontoxicity and ease of use. The Ag PNPs were formed by annealing sputtered Ag ultra-thin films and were subsequently capped by a spin-coated PDMS layer. We investigate the factors that affect their plasmonic behavior, such as the PNP size, the annealing conditions and the surrounding environment. In order to achieve broadband absorption, we developed PDMS/Ag(PNPs) multilayers with graded PNP size. Thus, we demonstrate the significance of the stacking sequence of various plasmonic layers sandwiched between PDMS layers and its potential for tailoring the plasmonic response of multilayer structure. As a demonstration of this approach, we deposited a specially designed multilayer structure, whose optical extinction resembles the solar emission spectrum.
Keywords: Nanocomposites; PDMS; Plasmonics; Silver; Solar absorption